Economic and clinical evaluation of vagus nerve stimulation therapy. (20th June 2019) - Kopciuch, Dorota; Barciszewska, Anna‐Maria; Fliciński, Jędrzej; Paczkowska, Anna; Winczewska‐Wiktor, Anna; Jankowski, Roman; Steinborn, Barbara; Nowakowska, Elżbieta
Abstract : Objectives: The medical and social care of drug‐resistant epilepsy (DRE) entails significant costs. Approximately 30 to 40 percent of patients with DRE who underwent vagus nerve stimulator (VNS) implantation achieve an above 50 percent reduction in seizure frequency. The study objective was to analyze the effect of VNS on clinical effects improvement and therapy cost reduction in patients with DRE over a 2‐year follow‐up period. The second purpose of the study was to compare average costs of VNS treatment of patients with DRE in selected countries, taking into account the purchasing power parity. Materials and Methods: The study included all the patients who had VNS implanted at our department between 2014 and 2018. Data on clinical events and medical costs were collected prospectively and obtained from medical documentation. We also reviewed relevant literature on costs of VNS therapy in patients with DRE from the last 18 years. Results: Resource utilization and epilepsy‐related events were reduced during the follow‐up period compared to the baseline. Average total cost was estimated at EUR 7703.59 in year 1 and at EUR 7108.38 in year 2 following VNS implantation. Average direct costs of VNS treatment of patients with DRE over the last 18 years varied between the countries and ranged from EUR 24 790.43 in the United States to EUR 64.84 in the United Kingdom. Conclusion: Vagus nerve stimulator is a cost‐effective therapy yielding measurable clinical and therapeutic outcomes over the long term. Moreover, the analysis contained in this review highlights the poor consensus of methodological approaches.